1993
DOI: 10.1038/bjc.1993.7
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the proto-oncogenes c-met and c-kit and their ligands, hepatocyte growth factor/scatter factor and stem cell factor, in SCLC cell lines and xenografts

Abstract: We examined a panel of 25 small cell lung cancer (SCLC) cell lines and nude mouse xenografts for expression of the proto-oncogenes c-met and c-kit, and for expression of the corresponding ligands, hepatocyte growth factor (HGF) (also known as scatter factor (SF)), and stem cell factor (SCF), respectively. Expression of mRNA was detected by Northern blotting, and c-met and c-kit protein expression was detected by Western blotting and immunocytochemistry. c-met and c-kit mRNA was expressed in 22 of the examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
0
4

Year Published

1993
1993
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(72 citation statements)
references
References 47 publications
(57 reference statements)
3
64
0
4
Order By: Relevance
“…In SCLC, c-Kit RNA and protein is found overexpressed in tumor cell lines and primary tumor tissues, and it is hypothesized that there is an SCF/c-Kit autocrine loop involved in this cancer. 12,38,41,42 Our data highly support the function of c-Kit in this cancer type given that CK6 antagonized signaling in SCLC tumor cell lines and blocked their growth in vitro and in vivo. We analyzed c-Kit expression in primary lung tumor samples by immunohistochemistry and found 46% of SCLC tumors were c-Kit positive, consistent with previous reports of 37 to 86% of SCLC tumors being positive for c-Kit.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…In SCLC, c-Kit RNA and protein is found overexpressed in tumor cell lines and primary tumor tissues, and it is hypothesized that there is an SCF/c-Kit autocrine loop involved in this cancer. 12,38,41,42 Our data highly support the function of c-Kit in this cancer type given that CK6 antagonized signaling in SCLC tumor cell lines and blocked their growth in vitro and in vivo. We analyzed c-Kit expression in primary lung tumor samples by immunohistochemistry and found 46% of SCLC tumors were c-Kit positive, consistent with previous reports of 37 to 86% of SCLC tumors being positive for c-Kit.…”
Section: Discussionsupporting
confidence: 52%
“…These findings demonstrate sensitivity of c-Kit expressing and SCF responsive tumor cell lines to the antagonistic effects of CK6 which may potentially occur through neutralization of SCF/c-Kit autocrine/ paracrine loop pathways. 38 We also considered the possibility of additional CK6 antibody mediated mechanisms of action, such as receptor degradation. CK6 internalizes within several hours of binding to c-Kit positive cells but does not induce significant receptor degradation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that HGF is produced by non-parenchymal hepatic cells including Kupffer cells (Noji et al, 1990), endothelial cells (Stoker et al, 1987;Shima et al, 1991), fibroblasts and fat-storing cells in the liver (Ramadori et al, 1992;Schirmacher et al, 1992), endothelial cells in the lung Yanagita et al, 1992). Experimentally, tumour cells are also known to produce HGF; HGF or mRNA encoding this factor has been detected in fibrosarcoma (Stoker et al, 1987), lung cancer (Yoshinaga et al, 1992;Rygaard et al, 1993;Tsao et al, 1993); hepatoma (Miyazaki et al, 1991) and pancreatic cancer cells (Hirota et al, 1993). Other normal tissues, such as the pancreas, small intestine, thyroid, brain and submaxillary salivary gland are also known to produce HGF (Zarmegar et al, 1990;Wolf et al, 1991).…”
Section: Methodsmentioning
confidence: 99%
“…1 Between 79% and 88% of SCLC cell lines were found to express c-kit and 57-76% of the cell lines expressed both c-kit receptor and the ligand SCF. 1,2 After binding of the ligand dimer, 2 adjacent kit receptors form a homodimer, leading to activation of the intracellular kit kinase domains. As a result, tyrosine residues are cross-phoshorylated by the activated kinases of the opposed homodimer partner.…”
mentioning
confidence: 99%